Analisis Kualitas Pelayanan Program Jaminan Kesehatan Nasional BPJS Kesehatan pada Rumah Sakit Umum Daerah Kota Madiun - Andy Widyatmoko; Puji Astuti; Yuwanto . (Journal of Politic and Government Studies, 2014)
AbstractIndonesia is a developing country that wants to be developed later. Tobecome developed countries certainly Indonesia must have qualified humanresources. The quality of a person is not only determined by the level ofeducation but also of health. If someone is healthy then it will work fine.Therefore, the State is obliged to pay attention to the health of any of itscitizens, especially for the poor, one of which is to create a program JaminanKesehatan Nasional (JKN). This program may be said its implementation couldbetter if in fulfilling basic needs of public health services. So the quality isexpected by society.This research is done using methods quantitative a questionnaire surveyand spreading to the patient Jaminan Kesehatan Nasional service users toobtain data of hope and reality service quality Jaminan Kesehatan Nasionalprograms. Besides the research is done in RSUD Kota Madiun particularly inpatients hospitalized class III.The result showed that of answer the respondents about service quality ofprogram Jaminan Kesehatan Nasionail in RSUD Kota Madiun overall goodenough but, some indicators service according to patient still not good and notin conformity with expectation patients. Of research results are also obtainedwhat service indicators a priority improvements to enhance the quality ofservice and enhancing customer satisfaction index. To improve the quality ofthe services of course between parties RSUD Kota Madiun, local governmentsand citizens of Kota Madiun should mutually synergize.Keywords : Health, Public Services, The Quality Of Public Services, JaminanKesehatan Nasional